Sagot :
Explanation:
a) 1 × 10^{-3} m
Given:
λ = 1 \times 10^{-3} \: \text{m}λ=1×10
−3
m
Required:
f
Equation:
f = \frac{c}{λ}f=
λ
c
Solution:
f = \frac{3.00 \: \times \: 10⁸ \: \frac{\text{m}}{\text{s}}}{1 \: \times \: 10^{-3} \: \text{m}}f=
1×10
−3
m
3.00×10⁸
s
m
Answer:
f = 3 \times 10¹¹ \: \text{Hz}f=3×10¹¹Hz
b) 3.8 × 10^{-7} m
Given:
λ = 3.8 \times 10^{-7} \: \text{m}λ=3.8×10
−7
m
Required:
f
Equation:
f = \frac{c}{λ}f=
λ
c
Solution:
f = \frac{3.00 \: \times \: 10⁸ \: \frac{\text{m}}{\text{s}}}{3.8 \: \times \: 10^{-7} \: \text{m}}f=
3.8×10
−7
m
3.00×10⁸
s
m
f = 7.9 \times 10¹⁴ \: \text{Hz}f=7.9×10¹⁴Hz